THE EFFECT OF ACCOUNTABILITY, TRANSPARENCY, AND SERVICE QUALITY TOWARD LOYALTY OF ZAKAT PAYERS - Izhar Allessandria Mardini; Bambang Agus Pramuka; Negina Kencono Putri (OIKONOMIKA : Jurnal Kajian Ekonomi dan Keuangan Syariah, 2020)
Zakat can become a significant source of state revenue. This can be realized if the people of Islam in Indonesia obedient in paying the zakat. Besides, the zakat institution in charge of managing the zakat must be honest, transparent and accountable in managing the zakat so that can increase the confidence of zakat payers (muzakki). But in reality, until this time there are still found a lack of potential for the payment of zakat in Indonesia. There are several factors that lead to loyalty of zakat payers that will increase zakat collection, such as accountability, transparency, and service quality applied by zakat management organization.This study aims to examine the effect of accountability, transparency, and service quality toward loyalty of zakat payers. This research is a quantitative study with primary data from questionnaires distributed to zakat payers of zakat management organization in Purwokerto. Sampling technique uses a convenience sampling method. There are 100 respondents that fulfilled questionnaires. Data analysis technique used is multiple regression analysis. The results of this study indicate that accountability, transparency, and service quality have a significant and positive effect toward loyalty of zakat payers.